NURSE ETHICAL DILEMMAS IN INPATIENT WARD of BALADHIKA HUSADA HOSPITAL JEMBER - Siti Amaliatul Khoiroh; Ahmad Rifai; Alfid Tri Afandi (Department of Nursing, Faculty of Health Sciencce, Universitas Brawijaya, 2020)
A ward nurse is a practitioner nurse who takes action according to standard operatingprocedures and prevention and identifies the state of the environment for 24 hours. Theworkload can lead to the emergence of attitudes that become complaints of patients,namely the emotional instability of nurses because of fatigue and high activity. Theimpact of ethical dilemmas experienced by nurses, one of which is the emotional impacton nurses such as anger, stress, frustration, and fear during the decision-making process.The research design is qualitative research with a phenomenological approach thataims to explore nurses’ perceptions and experiences of the ethical dilemma of nursingin the inpatient ward. A total of six participants involved in this study were selected bypurposive sampling technique. Participants were the practitioner nurses in the inpatientward of the Baladhika Husada Hospital in Jember. Colaizzi analysis method is used toconclude this study. The results obtained by five main themes: nurse knowledge andunderstanding, forms of ethical dilemmas experienced by nurses, ethical dilemmas relatedto ethical principles, actions when experiencing ethical dilemmas, and expectations fornurses. Continuing education regarding nurse ethical dilemmas in the implementationof professional nursing care is crucial to improve the quality of nurse performance whendelivering nursing care.